Analysis of Teacher Interpretation of the Depth and Breadth of Middle School Level Global Warming Material using "Content Representation" (CoRe) - Meili Yanti; Aulia Rahmadhani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Global warming is a material presented at the VII grade junior high school level. This material is very complex so it causes different interpretations by everyone when teaching it. Therefore, this research aims to analyze teachers' interpretations of the depth and breadth of global warming material contained in KD 3.9 of the 2013 Curriculum. This research was conducted descriptively using the Content Representation instrument to obtain information about teachers' interpretations. Participants in this study were junior high school 11  science teachers who are members of the MGMP community in Majene Regency, West Sulawesi. The results of this study indicate that teachers interpret KD 3.9 quite completely. This was obtained from the CoRe instrument where teachers fill in essential concepts to teach global warming material. The results show that teachers with more than 10 years of teaching experience have a greater variety of teaching methods and assessments in teaching global warming material. In addition, global warming materials were also obtained based on their depth and breadth.